SYSTEMATIC REVIEW WITH META-ANALYSIS - Barbosa Filho, Valter Cordeiro (Cenas Educacionais, 2024)
Systematic reviews with meta-analysis have massive potential for summarizing and evaluating scientific evidence. They address and answer specific complex issues relevant to society, such as those relating to Education and Health. Despite their importance, many studies using this method are conducted with significant methodological weaknesses, such as needing to evaluate the quality of the studies included critically. This text, therefore, represents a support resource for researchers seeking to acquire knowledge about systematic reviews with meta-analysis. To this end, the author of this work discussed the theoretical and methodological elements involved in planning, conducting, and publishing systematic reviews using meta-analysis techniques. He presented examples of studies that adopt appropriate and relevant methodological approaches. Nevertheless, some resources (references to methodological guidelines and digital platforms) have been described to support researchers in the operational path of this type of review. The author hopes this text will elucidate paths and possibilities for advancing scientific research using systematic review with meta-analysis in Brazil and other countries, focused on achieving scientific knowledge with quality and, therefore, social commitment.